SOCIO-ECONOMIC TRANSFORMATION OF FARMERS THROUGH DIVERSIFICATION OF FARMING BUSINESSES IN THE DIGITAL ERA - Abi Al Mukarrom (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This research aims to examine the socio-economic transformation of farmers through the diversification of farming businesses that are integrated with the use of digital technology. A descriptive qualitative approach was used with data collection techniques through in-depth interviews, participatory observations, and documentation studies in several agricultural areas in Indonesia. The results of the study show that farmers have begun to carry out various forms of diversification, such as processing agricultural products, integrating agriculture-livestock, and utilizing agricultural services. Digital technology is used for promotion, sales, and business management through e-commerce platforms, social media, and agricultural applications. The positive impacts that have emerged include increasing income, business independence, changing mindsets, and increasing the role of women in the farmer household economy. However, there are still obstacles such as limited digital infrastructure and low technological literacy. These findings underscore the importance of cross-sectoral support to create an inclusive and sustainable digital agriculture ecosystem. This transformation shows the great potential of modern agriculture in driving rural economic and social development in the digital age.